Theta-Defensins Inhibit High-Risk Human Papillomavirus Infection Through Charge-Driven Capsid Clustering - Skeate, Joseph G.; Segerink, Wouter H.; Garcia, Mauricio D.; Fernandez, Daniel J.; Prins, Ruben; Lühen, Kim P.; Voss, Féline O.; Da Silva, Diane M.; Kast, W. Martin (Frontiers in Immunology, 2020)
Persistent infection with high-risk human papillomavirus (hrHPV) genotypes results in a large number of anogenital and head and neck cancers worldwide. Although prophylactic vaccination coverage has improved, there remains a need to develop methods that inhibit viral transmission towards preventing the spread of HPV-driven disease. Defensins are a class of innate immune effector peptides that function to protect hosts from infection by pathogens such as viruses and bacteria. Previous work utilizing α and β defensins from humans has demonstrated that the α -defensin HD5 is effective at inhibiting the most common high-risk genotype, HPV16. A third class of defensin that has yet to be explored are θ-defensins: small, 18-amino acid cyclic peptides found in old-world monkeys whose unique structure makes them both highly cationic and resistant to degradation. Here we show that the prototype θ-defensin, rhesus theta defensin 1, inhibits hrHPV infection through a mechanism involving capsid clustering that inhibits virions from binding to cell surface receptor complexes.